Ship-based Trackline Geophysical Data (MGD77) from the Amundsen Sea, Antarctica acquired during the Nathaniel B. Palmer expedition NBP0901 (2009) (IEDA: Marine-Geo Digital Library, 2009)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler during Nathaniel B. Palmer expedition NBP0901 conducted in 2009 (Chief Scientist: Dr. Stan Jacobs). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise. Data were acquired as part of the project(s): Collaborative International Research: Amundsen Sea Influence on West Antarctic Ice Sheet Stability and Sea Level Rise, Shedding dynamic light on iron limitation: The interplay of iron limitation and dynamic irradiance conditions in governing the phytoplankton distribution in the Ross Sea, and Collaborative Research: Sampling the ocean - sea ice interaction in the Pacific center of the Antarctic Dipole, and funding was provided by NSF grant(s): OPP06-32282